2015
DOI: 10.1002/anie.201411348
|View full text |Cite
|
Sign up to set email alerts
|

Easy Access to the Copper(III) Anion [Cu(CF3)4]

Abstract: CuCl or pre-generated CuCF3 reacts with CF3 SiMe3 /KF in DMF in air to give [Cu(CF3 )4 ](-) quantitatively. [PPN](+) , [Me4 N](+) , [Bu4 N](+) , [PhCH2 NEt3 ](+) , and [Ph4 P](+) salts of [Cu(CF3 )4 ](-) were prepared and isolated spectroscopically and analytically pure in 82-99% yield. X-ray structures of the [PPN](+) , [Me4 N](+) , [Bu4 N](+) , and [Ph4 P](+) salts were determined. A new synthetic strategy with [Cu(CF3 )4 ](-) was demonstrated, involving the removal of one CF3 (-) from the Cu atom in the pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
95
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 120 publications
(99 citation statements)
references
References 53 publications
(45 reference statements)
4
95
0
Order By: Relevance
“…Despite the fact that stoichiometric amounts of 1 are used in this reaction, its synthesis can be easily scaled up. Although previous methods for the synthesis of 1 required either large excess of TMSCF 3 or tedious column chromatography purification, we found that it can be synthesized from a one‐step procedure and purified by crystallization in CH 2 Cl 2 . This allowed us to synthesize 1 in a large scale without column chromatography (Figure a).…”
Section: Methodsmentioning
confidence: 80%
“…Despite the fact that stoichiometric amounts of 1 are used in this reaction, its synthesis can be easily scaled up. Although previous methods for the synthesis of 1 required either large excess of TMSCF 3 or tedious column chromatography purification, we found that it can be synthesized from a one‐step procedure and purified by crystallization in CH 2 Cl 2 . This allowed us to synthesize 1 in a large scale without column chromatography (Figure a).…”
Section: Methodsmentioning
confidence: 80%
“…It is also appreciably longer than the Cu−C bond distance in [PPh 4 ][Cu(CF 3 ) 4 ] (195.1(3) pm av. ), but indistinguishable within the experimental error from the Au−C bond length in [NBu 4 ][Au(CF 3 ) 4 ] (208.0(7) pm av.) .…”
Section: Methodsmentioning
confidence: 99%
“…Simulations for these spectra are presented in Figure S6 and the parameters are summarised in Table S2. X-ray photoelectron spectroscopy (XPS) is particularly diagnostic of the oxidation state in copper complexes,a s shake-up satellite peaks are observed in the Cu 2p region of the spectrum for Cu II species,b ut are absent for Cu III derivatives. [24,25] Figure 4d shows the XPS spectra of the Cu corroles as compared to Cu-2 and [TBA][Cu(CF 3 ) 4 ], [26] which were studied as authentic Cu II To complement spectroscopic experiments,D FT calculations (B3LYP/6-311G(d,p) with toluene CPCM solvation) were performed for Cu-1 as ac losed shell 1 Cu(III) singlet, af erromagnetically coupled 3 Cu(II) corrole radical cation, and an antiferromagnetically coupled, broken symmetry 1 Cu(II) corrole radical cation (Tables S3-S5, Figure S7 and S8). TheB 3LYP functional has been used to study aw ide variety of copper complexes [28] and it has been shown for copper corroles to give the most accurate values of DE T-S when benchmarked against pure functionals or multiconfigurational methods.…”
Section: An Authentic Cumentioning
confidence: 99%